The Correlation Between Cognitive Function with the Quality of Life in the Elderly in Barusari Village South Semarang District - Aini, Dwi Nur (University of Muhammadiyah Malang, 2016)
The problem faced by the elderly as human aging process is a process and natural. Some problems and disorders that frequently arise or occur in the elderly is declining cognitive function. Cognitive decline in the elderly is usually preceded by decline of memory or memory (forgetfulness) and other cognitive mengggu real life activities. The purpose of this study was to find out: